Factors Affecting the Longevity of Femoropopliteal Bypasses - Richa, Handa; Sanjiv, Sharma (Journal of Hypertension and Cardiology, 2015)
A surgical review of factors influencing femoropopliteal bypass longevity, including lesion characteristics, techniques, graft materials, and post‑operative surveillance.
Keywords: femoropopliteal bypass; grafts; CLI; patency; graft failure.